(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Technology has significantly transformed education, making learning more accessible, engaging, and personalized. This article explores the role of digital tools and artificial intelligence (AI) in modern education, highlighting their benefits in improving teaching methodologies, student engagement, and overall learning outcomes.